2019
DOI: 10.1109/tfuzz.2019.2892921
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass Fuzzy Time-Delay Common Spatio-Spectral Patterns With Fuzzy Information Theoretic Optimization for EEG-Based Regression Problems in Brain–Computer Interface (BCI)

Abstract: Electroencephalogram (EEG) signals are one of the most widely used non-invasive signals in Brain Computer Interfaces (BCI). Large dimensional EEG recordings suffer from poor SNR (Signal to Noise Ratio). These signals are very much prone to artifacts and noise, so sufficient preprocessing is done on raw EEG signals before using them for classification or regression. Properly selected spatial filters enhance the signal quality and subsequently improve the rate and accuracy of classifiers, but their applicabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…To overcome this issue, numerous changes have been applied to the CSP. The common spatio-spectral pattern approach (CSSP) combines an FIR filter with a CSP algorithm and was observed to improve performance relative to pure CSP (Reddy et al, 2019). Common sparse spatio-spectral patterns (CSSSP) (Dornhege et al, 2006) are a comparatively more advanced procedure where the common spectral patterns across channels are investigated.…”
Section: Feature Extraction Approaches In Eeg-based Bci Systemsmentioning
confidence: 99%
“…To overcome this issue, numerous changes have been applied to the CSP. The common spatio-spectral pattern approach (CSSP) combines an FIR filter with a CSP algorithm and was observed to improve performance relative to pure CSP (Reddy et al, 2019). Common sparse spatio-spectral patterns (CSSSP) (Dornhege et al, 2006) are a comparatively more advanced procedure where the common spectral patterns across channels are investigated.…”
Section: Feature Extraction Approaches In Eeg-based Bci Systemsmentioning
confidence: 99%
“…A brain–computer interface (BCI) system provides a potential communication medium between the human and external world by transforming brain activity into control commands 1 . Electroencephalogram (EEG) signals are the potential input to the BCI system since it alters mainly with the human brain's distinct physiological and neurological conditions 2 . Motor imagery (MI) BCI activity refers to performing limb, tongue, or leg movements mentally without performing the task in reality 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is reported that there is an increase in oscillatory beta power and a decrease in alpha power of EEG activity due to limb movement 5 . The capability to detect MI activity through EEG signals enables a BCI system to control assistive applications to support disabled people or patients suffering from motor impairments such as multiple sclerosis, amyotrophic lateral sclerosis, etc 2,6 . However, intrinsic nonstationarity and nonlinearity within EEG activity make processing and information extraction a tedious task 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most common procedures include using the Fast Fourier transform (FFt) to transform the EEG signals to the frequency domain [8], [9], [10] and the Meyer wavelet transformation [11], [12]. There have also been many different fuzzy approaches to the BCI problem [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%